شمولية النُّصوص التشريعية للمستجدات الفقهية من خلال أبعاد أربعة: دراسةٌ أصوليةٌ = The comprehensiveness of legislative divine texts upon contemporary juristic issues through four dimensions: an uṣūlī study - Mat Jubri@Shamsuddin, Mustafa; Sitiris, Miszairi (Mehir Vakfi, 2019)
نزلت الرسالة الأخيرة من الرسالات السماوية في صورة النصوص التي تتضمن مراد الله من عباده. وهذه النصوص التشريعية تحتوي على جميع أحكام الله في جميع الأشياء والقضايا. يهدف هذا البحث إلى الكشف عن شمولية النصوص التشريعية للمستجدات الفقهية، وذلك لأنه مما لا ريب فيه أن الله قد بيَّن الأحكام لجميع الأمور، لكن ما الدليل على ذلك؟ وما المسائل المستجدة التي تنضوي في نصوص الشارع؟ وما الأبعاد الأربعة في النصوص التشريعية التي تحقق شمولية كلام الشارع لهذه المستجدات؟ هذا البحث يعتمد على المنهج الاستقرائي التحليلي للإجابة عن هذه الأسئلة. The final revelation has been sent in the form of texts which contain God’s intentions towards His servants. These legislative texts are characterized as the last scripture of God to all mankind which comprehends legal rulings for all issues and problems. This research aims to ascertain the comprehensiveness of legislative divine texts upon contemporary juristic matters. It is indisputable that God has described rulings for everything, however, what are the pieces of evidence that denote this matter of fact? What kind of contemporary issues that have been tackled by the divine texts? And what are these four dimensions of legislative texts that realize their comprehensiveness upon contemporary juristic issues? This study will use an analytical method for resolving these questions.